The possibility of philosophical understanding reflections on the thought of Barry Stroud - Bridges, Jason; Kolodny, Niko.; Wong, Wai-hung. (New York : Oxford University Press, 2011)
Barry Stroud's work has had a profound impact on a very wide array of philosophical topics, but there has heretofore been no book-length treatment of his work. The current collection aims to redress this gap, with 13 essays on Stroud's work, all but one new to this volume.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Philosophy; Stroud, Barry